The effect of pramlintide, an antidiabetic amylin analogue, on angiogenesis-related markers in vitro - Leila Safaeian; Golnaz Vaseghi; Mina Mirian; Mehdi Firoozabadi (Wolters Kluwer Medknow Publications, 2020)
Background and purpose: Irregularities of angiogenesis may participate in the pathogenesis of diabetes complications. Pramlintide is an amylin analogue administered for the treatment of type 1 and type 2 diabetes. The present investigation aimed at surveying the effect of pramlintide on angiogenesis-related markers in human umbilical vein endothelial cells (HUVECs). Experimental approach: The proliferation of cells was assessed using 3-(4,5-dimethylthiazol-2-yl)-2,5- diphenyltetrazolium bromide (MTT) method. The effect of pramlintide on migration was estimated by Transwell® assay. in vitro evaluation of angiogenesis was performed by tube formation assay. The secretion of vascular endothelial growth factor (VEGF) to the supernatant of HUVECs was measured by an enzyme- linked immunosorbent assay (ELISA) kit. All experiments were performed in triplicate. Findings / Results: Pramlintide exhibited no inhibitory effect on HUVECs proliferation. It significantly increased cell migration at the concentration of 1 μg/mL. Pramlintide (1 μg/mL) also enhanced average tubules length, size, and the mean number of junctions. However, there was not any significant change in VEGF release from HUVECs. Conclusion and implications: Findings of this research revealed the effect of pramlintide on angiogenesis- related markers via enhancing migration and tubulogenesis in vitro, suggesting a worthwhile proposition for further clinical researches on improving vascular complications and healing of diabetic wounds.